Characterisation of Spray Development from Spark-Eroded and Laser-Drilled Multihole Injectors in an Optical DISI Engine and in a Quiescent Injection Chamber - Butcher,AJ; Aleiferis,PG; Richardson,D (SAE Technical Paper Series, 2015)
This paper addresses the need for fundamental understanding of the mechanisms of fuel spray formation and mixture preparation in direct injection spark ignition (DISI) engines. Fuel injection systems for DISI engines undergo rapid developments in their design and performance, therefore, their spray breakup mechanisms in the physical conditions encountered in DISI engines over a range of operating conditions and injection strategies require continuous attention. In this context, there are sparse data in the literature on spray formation differences between conventionally drilled injectors by spark erosion and latest Laser-drilled injector nozzles. A comparison was first carried out between the holes of spark-eroded and Laser-drilled injectors of same nominal type by analysing their in-nozzle geometry and surface roughness under an electron microscope. Then the differences in their spray characteristics under quiescent conditions, as well as in a motoring optical engine, are discussed on the basis of high-speed imaging experiments and image processing methods. Specifically, the spray development mechanism was quantified by spray tip penetration and cone angle data under a range of representative low-load and high-low engine operating conditions (0.5 bar and 1.0 bar absolute, respectively), as well as at low and high injector body temperatures (20 °C and 90 °C) to represent cold and warm engine-head conditions. Droplet sizing was also performed with the two injectors using Phase Doppler Anemometry in a quiescent chamber.